Carboxymethyl cellulose-based superabsorbent hydrogels containing carboxymehtyl β-cyclodextrin for enhanced mechanical strength and effective drug delivery. (August 2018) - Jeong, Daham; Joo, Sang-Woo; Hu, Yiluo; Shinde, Vijay Vilas; Cho, Eunae; Jung, Seunho
Graphical abstract: Highlights: The superabsorbent CMC-based hydrogel containing cmβCD was successfully synthesized. The storage modulus of cmβCD/CMC gel was about eight-fold higher than CMC gel. The cmβCD/CMC gel obtained displayed high performance in compressive strength. The cmβCD/CMC-based hydrogel enhanced the drug-loading capacity due to complexation. The cmβCD/CMC gel has non-cytotoxicity on human dermal fibroblast cell. Abstract: Carboxymethyl cellulose (CMC)-based hydrogels have superabsorbent properties but low mechanical strength. Variation of other hydrogel components might improve the mechanical strength, but has been occasionally seen to decrease the swelling and drug-loading capacity. To address these problems, we designed a dual-component system, consisting of both carboxymethyl β-cyclodextrin (cmβCD) and CMC. We synthesized the hydrogels by crosslinking βCD or cmβCD with both cellulose (CEL) and CMC to evaluate their intrinsic mechanical strength and swelling capacity. The characteristic structure and morphology of each hydrogel was determined by Fourier- transform infrared spectroscopy, solid-state nuclear magnetic resonance spectroscopy, and field emission scanning electron microscopy. The storage modulus of the cmβCD/CMC gel was nearly eight-fold higher than that of the CMC gel only in rheology tests; the compressive strength was also enhanced while still retaining high swelling ability. We also investigated the drug-loading capacity and subsequent release properties, using tetracycline as a drug model. The cmβCD/CMC hydrogels showed the most effective tetracycline-loading capacity with the highest antibacterial activity among all hydrogels. They also showed the highest mechanical strength and the best drug release properties apart from the appreciable swelling capacity. Furthermore, cmβCD/CMC hydrogels are non-cytotoxic towards human dermal fibroblasts, suggesting their safe use as nontoxic, bio-friendly, and effective drug delivery systems.